Why Lifelong Learning - Güneri, Mukadder (European Journal of Social Science Education and Research, 2018)
Mankind has learned many things and has trained himself not knowing in the prehistoric times because of necessity by means of trial and error. He learned to learn while giving human life struggle that they taught what they learned to make their lives easier for those who come after them. So the real reason for learning is the needs and continuity. These needs have developed parallel to the development of mankind and continue to develop today. Learning in this development process is institutionalized. On the other hand, learning in today’s world has gained a new dimension. The wider network of Internet and digital media has removed the boundaries of learning, time, space and age. Today, when we look at people’s education and teaching life in terms of people, institutions and the environment, we can separate five stages: Childhood, Mother, Mother and Father, Brother, Aunt, Uncle, Grandmother, grandfather,Other family members, Pre-school, Primary School, Various courses, Various activities; Puberty, Family members,.In the current environment,.High School, Various courses and studies; Youth Family members, In the current environment,.Universities and colleges,.Various courses and studies;.Maturity, Family members,.In The current environment,.Working environment, Courses,.Activities; After Maturity,.Sharing knowledge and experience,.Evaluation of knowledge and experience in today and tomorrow, Events for quality living, Travels and such. In this article, the answer to the question "why life-long education and teaching" was sought in classical method.